Nutrition literacy assessment in older adults: a scoping review of measurement tools - Ren, Yuxiao; Liu, Yahan; Liu, Kai; Jin, Runhao (Frontiers in Nutrition, 2025)
IntroductionNutritional diseases, common among the elderly, are profoundly affected by nutrition literacy. Nutrition literacy influences dietary habits and behaviors; therefore, developing nutrition literacy is essential for alleviating various illnesses and enhancing quality of life. This study sought to perform a scoping review to find and compare techniques for assessing nutrition literacy in older persons and identify any gaps in this area of scholarship.MethodsA comprehensive search of seven internet databases, including PubMed, Web of Science, the Cochrane Library, Wanfang, China Biology Medicine disc (CBM), China National Knowledge Infrastructure (CNKI) and VIP Database for Chinese Technical Periodicals (VIP), resulting in 1,995 articles. In addition, additional relevant studies were retrieved from the identified articles’ references. Ultimately, 14 publications were included, encompassing a total of 12 nutrition literacy evaluation instruments.ResultsThe Simplified Nutrition Appetite Questionnaire (SNAQ), and Nutrition Literacy Assessment Tool (NLAT) were identified as unidimensional instruments, while the other tools had multidimensional attributes. Of the 11 instruments assessed for reliability, the Portuguese version of the Mini-Nutritional Assessment (MNA Portuguese Version) was validated exclusively for validity, lacking a reliability evaluation. Moreover, the NLAT underwent just reliability testing, with no validity assessment performed. We observed that current assessment tools have shortcomings in terms of cultural appropriateness and need further validation. Most current techniques primarily focus on fundamental nutritional knowledge, overall nutritional status, and dietary choices, providing wide-ranging applicability. However, the existing assessment tools exhibit limitations regarding their applicability, indicator systems, and assessment content for elderly patients with chronic diseases, inadequately addressing the specific issues associated with these conditions.ConclusionTo address clinical nutritional requirements, it is essential to enhance the cross-cultural validation of tools via multidisciplinary translation teams and adherence to international guidelines, thereby improving their applicability across diverse populations. There is an immediate necessity to develop adaptable and customizable assessment instruments for certain diseases in the senior population. These tools should incorporate indicators of nutritional knowledge relevant to particular diseases, along with dynamic monitoring indicators of nutritional status, to enhance personalized nutritional management support for elderly. The integration of artificial intelligence technology into these tools can enhance their optimization, leading to improved accuracy and effectiveness in clinical nutritional practices for elderly care.